Sleep Quality and Social Jetlag in Young Adults During the Social Distancing Caused by COVID-19 - Cristina Salles; Katie Moraes Almondes; Matheus Araújo; Iohana Marques; Lucas Haine Gonzaga; Miguel Meira-e-Cruz; Carolina Aguiar; Cristiane Costa Dias (Sleep Science, 2023)
Introduction: This study aimed to evaluate the sleep quality and the Social Jetlag frequency in young adults during social distancing because of COVID-19.